2008
DOI: 10.1111/j.1438-8677.2008.00062.x
|View full text |Cite
|
Sign up to set email alerts
|

The mechanisms of refilling of xylem conduits and bleeding of tall birch during spring

Abstract: Seasonal variations in osmolality and components of xylem sap in tall birch trees were determined using several techniques. Xylem sap was extracted from branch and trunk sections of 58 trees using the very rapid gas bubble-based jet-discharge method. The 5-cm long wood pieces were taken at short intervals over the entire tree height. The data show that large biphasic osmolality gradients temporarily exist within the conducting xylem conduits during leaf emergence (up to 272 mosmol x kg(-1) at the apex). These … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
56
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(62 citation statements)
references
References 48 publications
5
56
1
Order By: Relevance
“…The daily increase in the P p values has been observed in a huge number of crop species (e.g., wheat, maize, canola (Brassica napus), grapevine, citrus, olive, banana, forest trees etc. ; Westhoff et al 2008, Rüger et al 2010b, 2013, Bramley et al 2012) and can clearly be correlated with increasing loss of leaf turgor following watering termination. The upward shift in the baseline signal, i.e.…”
Section: Drought and Salinity Effects On Turgor Pressurementioning
confidence: 96%
See 2 more Smart Citations
“…The daily increase in the P p values has been observed in a huge number of crop species (e.g., wheat, maize, canola (Brassica napus), grapevine, citrus, olive, banana, forest trees etc. ; Westhoff et al 2008, Rüger et al 2010b, 2013, Bramley et al 2012) and can clearly be correlated with increasing loss of leaf turgor following watering termination. The upward shift in the baseline signal, i.e.…”
Section: Drought and Salinity Effects On Turgor Pressurementioning
confidence: 96%
“…Even though patch pressure, P p , measurements are performed on a single leaf level, whereas the balancing pressure values, P b , measured with the pressure chamber data are based on multiple leaves, there is generally a quite good overall correlation between both parameters ( Figure 2; Westhoff et al 2008, Bramley et al 2012. Concomitant direct measurements of the cell turgor on many plant species (using the microcapillary cell turgor pressure probe) have revealed that the dependency of both parameters on cell turgor pressure can be fitted by Eq.…”
Section: Magnetic Probe Versus Pressure Chamber Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been various earlier observations of hydrophobic interior surfaces in xylem conduits based on a variety of methods, including microscopic stains (Laschimke, 1989;McCully et al, 2014), electron microscopy (Schneider et al, 1999;Wagner et al, 2000), experiments with organic solvents (Zimmermann et al, 2004;Westhoff et al, 2008;McCully et al, 2014), and observations of wetting angles in conduits (Zwieniecki and Holbrook, 2000;Kohonen, 2006;Brodersen et al, 2010;McCully et al, 2014). This body of evidence for plant species ranging from conifers to angiosperms, including monocots and eudicots, clearly shows that xylem conduit walls are partly hydrophobic.…”
Section: Hydrophobic Surfaces In Xylem Conduitsmentioning
confidence: 99%
“…However, critics have pointed to seemingly contradictory evidence, such as the existence of hydrophobic compounds in xylem (Schneider et al, 2003;Rösch et al, 2004;Zimmermann et al, 2004;Westhoff et al, 2008). These valid observations must be accounted for to fully understand how plants transport water via the cohesion-tension mechanism.…”
Section: Invited Special Articlementioning
confidence: 99%